Preparation method of sand washing mud-based baking-free brick and baking-free brick

By premixing the sand washing mud with fly ash, dehydrating it and mixing it with cement, using semi-dry method and pulse microwave activation technology, the problems of low strength and complicated process in the traditional sand washing mud treatment method are solved, and efficient preparation and elimination of Burning bricks improves the mechanical properties of the material and the efficiency of resource utilization.

CN119330667APending Publication Date: 2025-01-21HEFEI CEMENT RESEARCH AND DESIGN INSTITUTE CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411469859.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the prior art, the traditional treatment method of sand washing mud has problems such as low strength, complex process and high energy consumption, making it difficult to achieve efficient resource utilization.

Method used

By premixing sand-washed mud with fly ash, dehydrating it to the target moisture content, and then mixing it with cement, semi-dry method and pulse microwave activation technology are used to form modified sand-washed mud-based non-burning bricks.

Benefits of technology

It improves the preparation efficiency of sand washing mud, enhances the mechanical properties and durability of unfired bricks, realizes the dual solid waste resource utilization of fly ash and sand washing mud, and reduces the environmental burden.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330667A_ABST
    Figure CN119330667A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a sand washing mud-based baking-free brick, the method comprises the following steps: pre-mixing sand washing mud with fly ash to obtain modified sand washing mud, then carrying out semi-dry dehydration treatment on the modified sand washing mud, and mixing with cement to obtain a premix, the water content of the modified sand washing mud after the semi-dry dehydration treatment is 15-20%; loading the premix into a mold, and carrying out compression molding to obtain a baking-free brick mold blank; and activating the baking-free brick mold blank by using pulse microwaves to obtain the sand washing mud-based baking-free brick. Therefore, the baking-free brick prepared by the preparation method disclosed by the invention has the advantages of high forming speed, high compressive strength and no need of a long-time autoclaved curing process, the forming period is greatly prolonged, and the large-scale yield is favorably increased. The raw materials are rich in source, double solid waste resource utilization of the fly ash and the sand washing mud can be achieved, waste is turned into wealth, and the environmental burden is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of raw unburned brick production, in particular to a method for preparing washed sand mud-based unburned bricks. Background Art

[0002] With the vigorous development of industrialization and urbanization in my country, the demand for building materials such as sand and gravel has risen sharply. However, due to the gradual depletion of natural resources and the continuous construction of infrastructure, the contradiction between the supply and demand of natural sand has become increasingly acute. Therefore, due to the characteristics of abundant sources and controllable quality, artificial sand has quickly become a substitute for natural sand. Due to the limitations of raw material sources, crushing and production technology conditions, artificial sand will inevitably produce powder particles (stone powder and mud powder) during the production process, which will have a negative impact on the quality of concrete prepared by artificial sand. Therefore, in order to obtain high-quality artificial sand, sand and gravel enterprises need to clean the soil on the surface of the mined sand and gravel, as well as the stone powder and mud powder in the process of preparing artificial sand during the production process. The large amount of mud and water mixture produced in this way is collectively referred to as sand washing mud.

[0003] However, due to the characteristics of high water content, high clay content, and poor engineering properties, the disposal and resource utilization of sand washing mud are difficult and the methods are difficult to unify. At present, the traditional treatment methods of sand washing mud mainly include engineering backfill, low-lying landfill, mine backfill, etc. Although these methods are easy to operate and have a short treatment cycle, they mainly rely on the absorption capacity of downstream receiving points, cannot be recycled, and are not sustainable. Therefore, the recycling of sand washing mud resources has become a hot topic of research at home and abroad.

[0004] Using a curing agent to solidify the sand-washing mud and then use it to produce unburned brick building materials is one of the important ways to recycle the sand-washing mud. This unburned brick can be widely used in road infrastructure construction, greening projects, underground landfills, flood control and revetment projects, environmental restoration projects, and decorative landscape projects. There are two traditional ways to add curing agents: wet and dry. The wet method is to dilute the sand-washing mud into a slurry by adding additional water, and then add the curing agent. Although this method is easy to evenly disperse the curing agent, the strength of the cured body after hardening is low and cannot meet the application requirements; the dry method is to dry and crush the sand-washing mud, and then add the curing agent. This method is complex and energy-intensive. In addition, since the sand-washing mud has low activity and forms hard particles after drying, it is difficult to evenly mix with curing agents such as cement, which affects resource utilization. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a method for preparing sand-washing mud-based unfired bricks, which dehydrates the sand-washing mud to a target moisture content and then performs subsequent solidification and activation, effectively overcoming the shortcomings of low intensity of the wet process, complex dry process and high energy consumption, while making full use of the moisture in the sand-washing mud, reducing the dehydration pressure by presetting the dehydration target, avoiding the repeated process of dehydrating first and then adding water, thereby improving the preparation efficiency of the sand-washing mud.

[0006] According to a first aspect of an embodiment of the present invention, a method for preparing a washed sand mud-based unfired brick comprises the following steps:

[0007] S1. Premixing sand washing mud with fly ash to obtain modified sand washing mud, and mixing the modified sand washing mud with an alkaline activator, wherein the concentration of the alkaline activator is 4 mol / L to 12 mol / L, and the mass of the alkaline activator is 40% to 60% of the mass of the fly ash. The alkaline activator is any one of sodium hydroxide, potassium hydroxide and water glass.

[0008] S2. The modified sand-washing mud is subjected to semi-dry dehydration treatment and then mixed with cement to obtain a premix, wherein the moisture content of the modified sand-washing mud after the semi-dry dehydration treatment is 15% to 20%.

[0009] The ratios of the sand washing mud, fly ash and cement satisfy the following relationship: the sand washing mud accounts for 70% to 80% by weight, the fly ash accounts for 10% to 15% by weight, and the cement accounts for 10% to 15% by weight.

[0010] The fly ash is Class I fly ash and Class II fly ash.

[0011] Specifically, since sand washing mud has low activity and tends to form hard particles after drying, it is difficult to mix evenly with curing agents such as cement, which affects resource utilization.

[0012] Therefore, in the above steps, the present invention can improve the sedimentation and dehydration performance of the sand washing mud by adding fly ash, wherein the fly ash has a porous honeycomb structure, can provide a large specific surface area and adsorption activity, can effectively adsorb moisture and fine particles, promote the sedimentation of larger particles, and accelerate the sedimentation process; at the same time, the dispersing effect of fly ash increases the porosity of the sand washing mud and enhances the dehydration effect, which is manifested in the accelerated filtration speed and reduced specific resistance, thereby helping to improve the dehydration efficiency of the sand washing mud.

[0013] Preferably, the round particles of fly ash can play a barrier role and reduce the interfacial bonding force. The more fly ash is added, the weaker the bonding force is, and the easier it is to break the soil. Capillary action and surface tension promote water to enter the gaps between particles, promote particle separation, increase volume and dispersibility, and the formation of a hydration layer further improves the dispersion effect, which is more conducive to subsequent uniform mixing with the curing agent.

[0014] In this way, fly ash can not only effectively solve the problem of high viscosity and difficulty in dispersion of sand washing mud, optimize the homogenization process of sand washing mud and curing agent, but also help to improve the dehydration efficiency of sand washing mud.

[0015] The present invention adopts a semi-dry method during dehydration, that is, the washed sand mud is dehydrated to the target moisture content, retaining a small amount of moisture, and then performing subsequent solidification. This not only effectively overcomes the shortcomings of the traditional dry process that is complex and energy-intensive, avoids the repeated process of first dehydrating and then adding water, and improves the preparation process efficiency of the washed sand mud-based unfired bricks, but also makes full use of the reserved part of the moisture in the washed sand mud, so that the washed sand mud is always in a better dispersed state, which is conducive to full mixing with the curing agent and improving the performance of the unfired bricks.

[0016] In addition, when solidifying the modified sand washing mud, the moisture in its components is fully utilized. That is, during the solidification process, the moisture participates in the hydration reaction of the cement. Among them, the tricalcium silicate, dicalcium silicate, tricalcium aluminate and tetracalcium aluminoferrite in the cement react with water to generate a series of hydration products. These products not only provide the necessary structural strength, but also improve the overall performance of the material by optimizing the microstructure.

[0017] In addition, the present invention utilizes an alkaline activator to activate fly ash, so that the volcanic ash effect of the fly ash can generate gelled hydration products, which is beneficial to improving the activity of sand washing mud. It is equivalent to replacing part of the cement with fly ash, thereby reducing the amount of cement, and further realizing the dual solid waste resource utilization of fly ash and sand washing mud.

[0018] S3, loading the premix into a mold and pressing it on a press at 10MPa-15MPa to obtain a mold for an unfired brick;

[0019] S4, after activating the unburned brick mold by pulse microwave, obtain the washed sand mud based unburned brick, wherein the pulse ratio PR of the pulse microwave is 2 to 12, each cycle lasts for 2 minutes, and 10 to 40 cycles are performed, wherein the pulse ratio PR=((t on +t off ) / t on ), t on is the power-on state of the microwave, t offThe microwave is in a power-off state; the microwave temperature range of the pulse microwave is 50°C to 80°C, the microwave power range is 2kW to 5kW, and the microwave operating frequency range is 245MHz to 433MHz.

[0020] Specifically, in the above steps, the microwave adopts an operating frequency in the microwave frequency range of 245MHz to 433MHz, which can enhance the heating effect on the unfired brick mold, and is conducive to achieving synchronous heating of the inside and outside of the unfired brick mold as a whole, so that the temperature of each part of the unfired brick mold is uniform, avoiding microstructural damage caused by stress differences due to the temperature difference inside and outside the unfired brick mold during the activation process, and realizing rapid solidification of the unfired brick mold while ensuring that the blocks have strength that meets the standards, the material size is stable, and there are no microcracks.

[0021] The present invention utilizes the thermal effect generated by pulsed microwaves to promote the hydration reaction of mineral phases such as tricalcium silicate and dicalcium silicate in cement. The generated products such as calcium silicate hydrate (CSH) and calcium hydroxide (Ca(OH)2) fill the slurry pores more quickly, reducing the number and size of capillaries, thereby reducing the total porosity of unfired bricks and improving their density and durability.

[0022] At the same time, the non-thermal effect (pulse effect) generated by pulse microwaves promotes the alkali-induced reaction of fly ash, promotes the dissolution and diffusion of SiO2 and Al2O3 in fly ash, accelerates the nucleation and growth of NASH gel and crystalline phase, and increases the contact area of ​​the reactants through instantaneous high energy input, accelerates the rate of alkali-induced reaction, and enables the unburned bricks to obtain higher early strength in a short time.

[0023] In addition, the unfired bricks naturally dissipate heat during the microwave shutdown period, effectively reducing the energy waste of continuous heating and enhancing operational flexibility. At the same time, they effectively reduce thermal stress and temperature gradients, significantly reducing the chance of internal cracks.

[0024] The second aspect of the embodiment of the present invention is an unburned brick, which is prepared by any of the above-mentioned preparation methods. The unburned brick has excellent mechanical properties and durability, and is conducive to being widely used in road infrastructure construction, greening projects, underground landfills, flood control and bank protection projects, environmental restoration projects, and decorative landscape projects. At the same time, it can promote the recycling of sand washing mud solid waste resources.

[0025] Beneficial effects:

[0026] In the preparation method of the present invention, the coupling effect between fly ash, sand washing mud and cement and the activation treatment of pulse microwave is used, so that excellent mechanical properties and durability can be obtained while greatly shortening the preparation time, greatly improving the preparation efficiency of sand washing mud-based unfired bricks, and simultaneously solving the problem of low strength caused by traditional wet processes and the problems of complex steps, repeated processes and high energy consumption in traditional dry processes. At least the steps of drying, grinding and adding water in the later stage are reduced, and the problem of low activity of sand washing mud and easy formation of hard particles after drying, which is difficult to mix evenly with the curing agent, is avoided.

[0027] The unburned bricks prepared by the preparation method of the present invention have fast forming speed, high compressive strength, and do not require a long autoclave curing process, which greatly improves the forming cycle and is conducive to increasing large-scale production. In addition, the raw material source is abundant, and the double solid waste resource utilization of fly ash and sand washing mud can be realized, turning waste into treasure and reducing the environmental burden. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0029] Figure 1 is a SEM image of the modified sand washing mud according to an embodiment of the present invention;

[0030] Figure 2 is a SEM image of the original sand washing mud according to an embodiment of the present invention;

[0031] Figure 3 is a curve diagram showing the effect of fly ash on the settling velocity of sand washing mud according to an embodiment of the present invention;

[0032] Figure 4 is a curve diagram showing the effect of fly ash on the filtration loss of sand washing mud according to an embodiment of the present invention;

[0033] Figure 5 is a curve diagram of the screening rate of a 0.30 mm sieve hole diameter according to an embodiment of the present invention;

[0034] Figure 6 is a curve diagram of the screening rate of a 1.18 mm sieve hole diameter according to an embodiment of the present invention;

[0035] Figure 7 Schematic diagram of fineness modulus according to an embodiment of the present invention. DETAILED DESCRIPTION

[0036] Embodiments of the present invention are described in detail below, and the embodiments described with reference to the accompanying drawings are exemplary.

[0037] Example 1

[0038] In this embodiment, the washed sand mud-based unburned bricks are prepared according to the following steps:

[0039] The sand washing mud is premixed with 10% of first-grade fly ash to obtain modified sand washing mud, and dehydrated to a moisture content of 15%, and then mixed with 10% of 42.5 general silicate cement, 12 mol / L NaOH solution and 40% of the mass of fly ash, and quickly stirred for 2 minutes until the mixture is uniform. The material is taken out and loaded into a mold, and formed on a press with a molding pressure of 15 MPa. After the test piece is demolded, the brick is transferred to a microwave reaction chamber, and the operating frequency of the microwave reaction chamber is set to 245 MHz, PR is 2, 10 cycles are performed, the temperature is controlled at 50°C, and the power is 5 kW. After activation, the unfired brick can be obtained.

[0040] Example 2

[0041] In this embodiment, the washed sand mud-based unburned bricks are prepared according to the following steps:

[0042] The sand washing mud is premixed with 15% of first-grade fly ash to obtain modified sand washing mud, and dehydrated to a moisture content of 20%, and then mixed with 15% of 42.5 general silicate cement, 4 mol / L NaOH solution with a mass of 60% of the mass of fly ash, and quickly stirred for 2 minutes until the mixture is uniform. The material is taken out and loaded into a mold, and formed on a press with a molding pressure of 10 MPa. After the test piece is demolded, the brick is transferred to a microwave reaction chamber, and the operating frequency of the microwave reaction chamber is set to 433 MHz, PR to 12, and 10 cycles are performed. The temperature is controlled at 80°C and the power is 2 kW. After activation is completed, unfired bricks can be obtained.

[0043] Example 3

[0044] In this embodiment, the washed sand mud-based unburned bricks are prepared according to the following steps:

[0045] The sand washing mud is premixed with 12% of first-grade fly ash to obtain modified sand washing mud, and dehydrated to a moisture content of 18%, and then mixed with 13% of 42.5 general silicate cement, 8 mol / L NaOH solution and 50% of the mass of fly ash, and quickly stirred for 2 minutes until the mixture is uniform. The material is taken out and loaded into a mold, and formed on a press. The molding pressure is 13 MPa. After the test piece is demolded, the brick is transferred to a microwave reaction chamber, and the operating frequency of the microwave reaction chamber is set to 300 MHz, PR is 12, 10 cycles are performed, the temperature is controlled at 65°C, and the power is 4 kW. After activation, the unfired brick can be obtained.

[0046] Comparative Example 1:

[0047] This example is a control group of the above-mentioned Example 2. The water content of the sand washing mud in the steps of Example 2 is changed from 20% to 40%, and the molding method is changed to casting molding. The specific method steps are as follows:

[0048] The sand washing mud is premixed with 15% of first-grade fly ash to obtain modified sand washing mud, and dehydrated to a moisture content of 40%, and then mixed with 15% of 42.5 general silicate cement and 4 mol / L NaOH solution accounting for 60% of the fly ash mass, and quickly stirred for 2 minutes to mix evenly. The material is taken out and put into a mold and allowed to stand until it can be demolded. After the test piece is demolded, the brick is transferred to a microwave reaction chamber, and the operating frequency of the microwave reaction chamber is set to 433 MHz, PR is 12, 10 cycles are performed, the temperature is controlled at 80°C, and the power is 2 kW. After activation is completed, unfired bricks can be obtained.

[0049] Comparative Example 2:

[0050] This example is a control group of Example 2, and the water content of the sand washing mud in the steps of Example 2 is changed from 20% to 0%. The specific method steps are as follows:

[0051] The sand washing mud is premixed with 15% of primary fly ash to obtain modified sand washing mud, and the sand washing mud is dehydrated to a moisture content of 0%. The dried sand washing mud is then ground and mixed with 15% of 42.5 general silicate cement and 4 mol / L NaOH solution accounting for 60% of the fly ash mass. The mixture is quickly stirred for 2 minutes until the mixture is uniformly mixed. Water is then added at a uniform rate, and the amount of water added is 15% of the sand washing mud. The material is taken out and loaded into a mold and allowed to stand until it can be demolded. After the test piece is demolded, the brick blank is transferred to a microwave reaction chamber, and the operating frequency of the microwave reaction chamber is set to 433 MHz, PR to 12, 10 cycles are performed, the temperature is controlled at 80°C, and the power is 2 kW. After activation, unfired bricks can be obtained.

[0052] Comparative Example 3:

[0053] This example is a control group of Example 2, except that the fly ash in the steps of Example 2 is replaced with 42.5 cement, and the addition of NaOH solution is removed. The remaining method steps remain the same as those of Example 2, namely:

[0054] First, dehydrate the washed sand mud to a moisture content of 20%, then add 70% of the dehydrated mud and 30% of 42.5 general Portland cement, stir quickly for 2 minutes until the mixture is evenly mixed, take out the materials and put them into a mold, and form them on a press with a molding pressure of 10 MPa. After the test piece is demolded, transfer the bricks to a microwave reaction chamber, set the operating frequency of the microwave reaction chamber to 433 MHz, PR to 12, perform 10 cycles, control the temperature at 80°C, use a power of 2 kW, complete activation, and you can get unfired bricks.

[0055] Comparative Example 4:

[0056] This example is a control group of Example 2, except that the pulse microwave activation in the steps of Example 2 is replaced by full-power microwave activation, and the remaining method steps remain the same as those of Example 2, namely:

[0057] The sand washing mud is premixed with 15% of first-grade fly ash to obtain modified sand washing mud, and dehydrated to a moisture content of 20%, and then mixed with 15% of 42.5 general silicate cement, 15% of first-grade fly ash, and 4 mol / L NaOH solution accounting for 60% of the fly ash mass, and quickly stirred for 2 minutes to mix evenly. The materials are taken out and loaded into a mold, and formed on a press. The molding pressure is 10 MPa. After the test piece is demolded, the brick is transferred to a microwave reaction chamber, and the operating frequency of the microwave reaction chamber is set to 433 MHz. The operation is 100 minutes, the temperature is controlled at 80°C, and the power is 2 kW. After the curing is completed, the unfired brick can be obtained.

[0058] Test example:

[0059] 1. Compressive strength

[0060] The compressive strength is measured according to GB / T 5348 standard. After the specimen is cured, it is tested using a 300kN constant stress pressure testing machine. The test loading speed is 2.4kN / s. During the test, the specimen is precisely placed in the center of the bearing pressure plate, while ensuring that the pressure-bearing surface of the specimen is perpendicular to its forming surface, and the pressure is continuously and steadily increased until the test is completed. After each test, the maximum pressure value reached is recorded. Each ratio of the specimen was tested three times independently, and the average value was taken as the result. The calculation formula for compressive strength is as follows:

[0061]

[0062] Where: fc is the compressive strength of the specimen (MPa), F is the load when the specimen is destroyed (N), and A is the area of ​​the pressure-bearing surface of the specimen (mm2).

[0063] 2. Water absorption

[0064] During the water absorption test, the sample is first dried in a constant temperature oven at 105°C for 24 hours. After the sample completely loses moisture, its dry weight is recorded as m0. Next, the dried sample is soaked in water at room temperature for 24 hours. After ensuring that the sample fully absorbs water, it is taken out and gently wiped dry on the surface, and its wet weight is recorded as m1. The water absorption rate is calculated as follows: Water absorption rate (%) = (m1-m0) / m0*100%.

[0065] 3. Wet and dry cycle

[0066] At the beginning of the test, the sample is first removed from the curing box, the water droplets on the surface are wiped off, and the initial mass and unconfined compressive strength of the sample are measured. Subsequently, the test officially begins, and the weighed specimen is placed in an oven controlled at 60±3℃ for 24 hours. The sample is taken out and left to stand at room temperature for 1 hour to allow the sample temperature to return to ambient temperature. Next, sufficient deionized water is added to the sample to ensure that the sample is completely covered with water, and then the beaker containing the sample and water is placed in an indoor environment at 20±2℃ for 23 hours. After completing this series of operations, the sample is carefully removed and the surface debris is rinsed off with deionized water, the integrity of the sample and any potential cracks or damage are inspected, and the mass of the solids remaining in the waste liquid in the beaker is measured to complete a dry-wet cycle. This process will be repeated until a total of 12 dry-wet cycles are completed.

[0067] Finally, the samples were subjected to compressive strength tests and mass loss rate tests.

[0068] 4. Freeze-thaw cycle

[0069] The freeze-thaw cycle test of washed sand mud solidification body is carried out in accordance with GBT 4111-2013 "Test methods for concrete blocks and bricks".

[0070] The experimental process begins with removing the cured solid specimen from the standard curing environment and then immersing it in a vacuum water saturator at 20±2℃ for 4 days. After the treatment, the surface moisture is thoroughly wiped dry, and then the mass of the saturated and dry surface is measured and recorded. The sample is then placed in a GLD fully automatic low-temperature slow freezing tester for freeze-thaw cycle resistance testing. The test is set to complete a freeze-thaw cycle every 6 hours. The specific process is: the specimen is frozen in an environment of -15℃ for 4 hours, and then moved to water at 15-25℃ for 2 hours to thaw. After the freeze-thaw cycle is completed, the cured specimen is taken out, its appearance changes are observed and recorded, and then the surface moisture is wiped dry again and its mass is measured.

[0071] Finally, the samples were subjected to compressive strength tests and mass loss rate tests.

[0072] The test results are shown in Table 1:

[0073] Table 1. Performance index test results of embodiments and comparative examples

[0074]

[0075] From the data of Example 2, Comparative Example 1 and Comparative Example 2 in the comparison table, it can be obtained that the new process for preparing unfired bricks by the preparation method proposed in the present invention has significantly improved compressive strength and durability compared with the wet process molding, and effectively overcomes the problem of low strength of wet molding.

[0076] Compared with dry molding, although there is not much difference in performance, the steps of drying, grinding and adding water in the later stage are reduced, which effectively overcomes the shortcomings of the dry process which is complicated and energy-intensive, avoids the repeated process of dehydration followed by adding water, and has higher preparation efficiency.

[0077] From the data of Example 2 and Comparative Example 3 in the comparison table, it can be obtained that the present invention can successfully replace part of the cement with fly ash while ensuring the mechanical properties and durability, thereby reducing the amount of cement used and making resource utilization of solid waste.

[0078] From the data of Example 2 and Comparative Example 4 in the comparison table, it can be obtained that the pulse microwave used in the present invention has improved mechanical properties and durability compared with full-power microwaves. This is because in addition to the thermal effect, the pulse microwave also produces a non-thermal effect (pulse effect) that promotes the alkali-excitation reaction of fly ash, promotes the dissolution and diffusion of SiO2 and Al2O3 in the fly ash, accelerates the nucleation and growth of NASH gel and crystalline phase, and through instantaneous high energy input, increases the contact area of ​​the reactants, accelerates the alkali-excitation reaction rate, and enables the unburned bricks to obtain higher early strength in a short time.

[0079] Experimental example:

[0080] (1) Sedimentation rate

[0081] This test selected the original undewatered sand mud with a moisture content of 94% and a fly ash content of 15%.

[0082] Before the test, the fly ash and sand washing mud were mixed thoroughly to ensure uniform composition. Then, the mixed slurry was poured into a 500 ml measuring cylinder and stirred continuously with a glass rod during the pouring process. In order to accurately evaluate the sedimentation characteristics, the supernatant volume was measured every 10 minutes.

[0083] (2) Dehydration performance

[0084] In this test, the original undewatered sand mud with a moisture content of 94% and a fly ash content of 15% were selected.

[0085] Before the test, the fly ash and sand washing mud were fully mixed to ensure uniform composition. After stirring evenly, the sand washing mud was slowly poured into the sample tube, and the initial mud surface height was set to 4 cm. Then, the valve was opened, the air pressure was adjusted to 20 kPa, and the filtration loss was recorded every 5 minutes.

[0086] (3) Dispersion performance

[0087] The modified sand washing mud was dried and dehydrated to a moisture content of 15% and 20%, wherein the fly ash content was 0%, 10%, 20%, 30% and 40%, respectively, and then transferred to a vibrating screen for dispersion test.

[0088] like Figure 3 and Figure 4 As shown, compared with the original sand washing mud slurry without fly ash, the sedimentation time of the sand washing mud slurry added with 20% fly ash was shortened by 37.5%, and the sedimentation rate was significantly improved. In addition, the filtration dehydration rate of the sand washing mud was significantly improved, and the time required for filtration was reduced by 33.3% compared with the sand washing mud without fly ash.

[0089] like Figure 5 and Figure 6 As shown, with the increase of fly ash content, the screening rate of 0.3mm sieve hole of modified fly ash sand washing mud also increases accordingly, and the screening rate of 1.18mm sieve hole increases with the increase of fly ash content.

[0090] like Figure 7 As shown, the fineness modulus shows the same trend as the 1.18 mm sieve aperture screening rate, indicating that with the increase in fly ash content, the coarse particles become fewer, the fine particles become more, and the dispersion performance becomes better.

[0091] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.

[0092] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A method for preparing washed sand mud-based unfired bricks, characterized in that: The method comprises the following steps: S1. Premixing sand washing mud with fly ash to obtain modified sand washing mud; S2, mixing the modified sand-washing mud with cement after semi-dry dehydration treatment to obtain a premix, wherein the moisture content of the modified sand-washing mud after semi-dry dehydration treatment is 15% to 20%; S3, loading the premix into a mold and pressing it into shape to obtain a mold base for an unfired brick; S4, activating the unfired brick mold by using pulse microwave to obtain washed sand mud-based unfired bricks.

2. The method for preparing a washed sand mud-based unburned brick according to claim 1, characterized in that: The sand washing mud accounts for 70% to 80% by weight, the fly ash accounts for 10% to 15% by weight, and the cement accounts for 10% to 15% by weight.

3. The method for preparing a washed sand mud-based unburned brick according to claim 2, characterized in that: In the step S1, after the sand washing mud and fly ash are premixed to obtain modified sand washing mud, the modified sand washing mud is mixed with an alkaline activator, wherein the concentration of the alkaline activator is 4 mol / L to 12 mol / L.

4. The method for preparing a washed sand mud-based unburned brick according to claim 3, characterized in that: The alkaline activator is any one of sodium hydroxide, potassium hydroxide and water glass.

5. The method for preparing a washed sand mud-based unburned brick according to any one of claims 1 to 4, characterized in that: The fly ash is Class I fly ash and Class II fly ash.

6. The method for preparing a washed sand mud-based unburned brick according to claim 1, characterized in that: The molding pressure range of the premix compression molding in step S3 is 10MPa to 15MPa.

7. The method for preparing a washed sand mud-based unburned brick according to claim 1, characterized in that: The pulse ratio PR of the pulse microwave in step S4 is 2 to 12, each cycle lasts for 2 minutes, and 10 to 40 cycles are performed, wherein the pulse ratio PR=((t on +t off ) / t on ), t on is the power-on state of the microwave, t off The microwave is powered off.

8. The method for preparing a washed sand mud-based unburned brick according to claim 1 or 7, characterized in that: The microwave temperature range of the pulse microwave is 50° C. to 80° C., the microwave power range is 2 kW to 5 kW, and the microwave operating frequency range is 245 MHz to 433 MHz.

9. A non-fired brick, characterized in that: An unburned brick prepared by the method for preparing washed sand mud-based unburned bricks according to any one of claims 1 to 8.

Citation Information

Cited By

  • Water-retaining aggregate with core-shell structure as well as preparation method and application of water-retaining aggregate

    CN121107731A